A systematic review of blood eosinophils and continued treatment with inhaled corticosteroids in patients with COPD. (July 2022) - Dalin, Dagmar Abelone; Løkke, Anders; Kristiansen, Pernille; Jensen, Charlotte; Birkefoss, Kirsten; Christensen, Hanne Rolighed; Godtfredsen, Nina Skavlan; Hilberg, Ole; Rohde, Jeanett Friis; Ussing, Anja; Vermehren, Charlotte; Händel, Mina Nicole
Abstract: Inhaled corticosteroid (ICS) in patients with chronic obstructive pulmonary disease (COPD) has been debated for 20 years. In our systematic literature review and meta-analysis, we addressed the following: Should patients with COPD and a blood eosinophil count (EOS) of, respectively, a) < 150 cells/μl, b) 150–300 cells/μl, and c) > 300 cells/μl continue treatment with ICS? Protocol registered in PROSPERO (CRD42020178110) and funded by the Danish Health Authority. We searched Medline, Embase, CINAHL and Cochrane Central on 22 nd July 2020 for randomized controlled trials (RCT) of ICS treatment in patients with COPD (≥40 years, no current asthma), which analyzed outcomes by EOS count and where >50% of patients used ICS prior. We used the GRADE method. Meta-analyzes for the outcomes were divided into EOS subgroups and analyzed for differences. We identified 11 RCTs with a total of 29, 654 patients. A significant difference (p < 0.00001) between the three subgroups' reduction of risk of moderate to severe exacerbation was found. Rate ratios for EOS counts: <150 cells/μL was 0.88 (95%CI: 0.83, 0.94); 150–300 cells/μL was 0.80 (95%CI: 0.69, 0.94); >300 cells/μL was 0.57 (95%CI: 0.49, 0.66). Overall, the certainty of the effect estimates was low to very low due to risk of bias, unexplained heterogeneity, few RCTs, and wide confidence intervals. A clear correlation was demonstrated between effect of continued ICS treatment (number of exacerbations, lung function, and quality of life) and increasing EOS count. Our meta-analyses suggested that treatment with ICS seemed beneficial for everyone except patients with EOS count below 150 cells/μl. Highlights: In COPD patients exists a correlation between effect of ICS and eosinophil. ICS might not be beneficial for COPD patients with eosinophil count <150 cells/μl. Exacerbation risk increased in patients with high eosinophil count when stopping ICS.